2010
DOI: 10.1021/jp101476g
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Physically Intuitive Reaction Coordinates from Transition Networks of a β-Sheet Miniprotein

Abstract: Simulations are important for understanding complex reactions, but their interpretation is challenging owing to the large number of degrees of freedom typically involved. To address this issue, various means for relating the dynamics of a stochastic system to its structural and energetic features have been introduced. Here, we show how two leading approaches can be combined to advantage. We use the network of transitions observed in a reversible folding/unfolding simulation of a 20-residue three-stranded antip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(69 citation statements)
references
References 29 publications
14
55
0
Order By: Relevance
“…Since the reaction coordinates are not identical, we matched their left and right boundaries to compare the FEPs. It is seen that the profiles are in good agreement, confirming that the sum of the bond distances 31 and the first principal coordinate determined with the HB PCA method (Sect. 2.2) can both serve as reaction coordinates for the overall description of the folding process.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Since the reaction coordinates are not identical, we matched their left and right boundaries to compare the FEPs. It is seen that the profiles are in good agreement, confirming that the sum of the bond distances 31 and the first principal coordinate determined with the HB PCA method (Sect. 2.2) can both serve as reaction coordinates for the overall description of the folding process.…”
Section: Resultssupporting
confidence: 75%
“…The bonds involved in g 1 (the upper panel) are exactly the bonds Qi et al have found most appropriate to describe folding of beta3s 31 , and Zheng et al have indicated as the bonds that make the major contribution to the first “diffusion” coordinate 43 . Moreover, the contributions of different bonds are approximately equal, as was assumed 31 and confirmed 43 previously. A nonzero projection of g 1 onto a bond indicates that g 1 changes as the length of the bond changes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The last conformations that come in equilibrium with the others are the Ch-curl conformations, which are less stable than the antiparallel β-strands and more difficult to form dynamically because of the distant N-and C-terminal strands. The observed hierarchy of the establishment of equilibrium between the characteristic conformations is in good agreement with the results of the previous studies 6,11,12,25,28,[30][31][32]45 and has allowed further insight into the process of beta3s folding. One issue of particular interest is the difference between the Cs-or and Ns-or pathways, which has been indicated in the early work 25 and confirmed in the later, the first-passage folding studies: 11,12 although Cs-or and Ns-or conformations are "symmetrical" in that each of them has one hairpin formed and the other unstructured, the Ns-or pathway prevails.…”
Section: Resultssupporting
confidence: 90%
“…[52] Other applications of the method included the study of a nucleotide flipping facilitated by O 6 -alkylguanine-DNA alkyltransferase [38] and the study of the folding of a 20-residue antiparallel-sheet miniprotein. [71]…”
Section: Committor-based Methodsmentioning
confidence: 99%